Імператив фіскальної солідарності - Андрущенко, Володимир Леонідович (УДФСУ, 2019)
Стаття присвячена розгляду поняття та явищ фіскальної солідарності як соціально гуманного імперативу сучасної епохи в опосередкованих через оподаткування фінансових взаєминах між державами, регіонами, поколіннями, окремими людьми. Саме цінності солідарності, зокрема й особливо фіскальної, належать До основоположних цінностей Євросоюзу. На основі міждисциплінарного фіскально-соціологічного методу дослідження сформульовано дефініцію фіскальної солідарності. Визначено її типи, вказано на авторів досліджень на цю тему, розкрито окремі фіскально-технологічні заходи солідарного характеру. Abstract. Introduction. Fiscal solidarity belongs to the fundamental values of the European Union. But studies on the topic of fiscal solidarity in the context of taxation doctrine are absent almost entirely in domestic Ukrainian publications. In the EU fiscal solidarity takes the form of interstate support by the principle “from a richer to a poorer” exercised through the EU common budget. Solidarity taxes at the national level are also used with a social target. Purpose. The goal of the article is to give impulse to domestic research on this topic. We intend to fill the emptiness of research on fiscal solidarity in Ukraine and further will investigate this actual topic. The aim is also to reveal the cognitive-analytical possibilities and the humane task of the phenomena of fiscal solidarity. Methods. The mighty interdisciplinary method of fiscal sociology has been used in this article for investigation of the nature and solidarity phenomena. Results. It was proved that the economic essence of fiscal solidarity consists in there distribution of always limited resources with the relating problems and contradictions. Fiscal solidarity embodies a most meaningful and realistic understanding of the functional role of modern taxation and public finances in general. The author formulated a definition of his own: Fiscal solidarity is the provision of some horizontal equalization of resource sufficiency on the principle of resource redistribution from richer to poorer members of a certain political, economic or social cohesion unity (individuals, regions or states) by financial operations of purposeful humanitarian and simultaneously business nature. Conclusion. A fundamental substantive feature of fiscal solidarity is its redistributive character, which gives rise to the inevitable contradiction between the feelings of solidarity by the side that gives the benefits of solidarity and between those who receives them. It is important that fiscal solidarity under present conditions has acquired the power and status of a categorical behavioral imperative at the level of interregional, state-personal and interpersonal financial interactions in the modern Ukraine.
Keywords: фіскальна солідарність, імператив, метод фіскальної соціології, податок солідарності, Євросоюз, Маастрихтський Договір, децентралізація, субсидіарність.; fiscal solidarity, imperative, method of fiscal sociology, solidarity tax, European Union, Maastricht Treaty, decentralization, subsidiarity.